Evaluation of polypus growth among fecal immunochemical test positive patients - Hyder, Chowdhury S.; Uddin, Azim; Jalal, Tanvir; Karim, Saiyeda S.; Taher, Abu; Nahar, Kamrun; Naznin, Kazi N.; Hossain, Shahadat (International Surgery Journal, 2023)
Background: Colorectal cancer is a difficult clinical condition to treat all over the world. Adenomatous polyps are thought to be cancer precursors. A colonoscopy is required to detect and confirm ulcerative colitis mucosal healing. Different screening procedures, including as colonoscopy, fecal immunochemistry test (FIT), guaiac fecal occult blood test (gFOBT), computed tomography (CT) colonography, and others, are used to detect polyps or ulcers early. Although the gold standard colonoscopy serves both diagnostic and therapeutic purposes, the FIT can identify advanced adenoma or established cancer, as well as the mucosal condition of ulcerative colitis. The FIT is a less costly approach for detecting colonic disease that is appropriate for our demographic. The aim of the study was to observe the type of polypus growth among FIT positive patients. Methods: This observational cross-sectional study was conducted at the department of colorectal surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The study duration was 1 year, from July 2019 to August 2020. At the initial stage, a total of 510 participants were selected among the patients attending the outdoor department of BSMMU colorectal surgery following the inclusion and exclusion criteria. Results: The male: female ratio was 1.7:1 in our study. 48.28% were from the age group of 50-59 years. The most common clinical presentation or symptom among the participants was constipation, observed in 81.03% of cases. 39.66% of the participants had abdominal pain, 32.76% had rectal mucus discharge, 12.07% had observed changes in their bowel movement, while 6.90% had a lack of appetite. Among the participants, 42 had pedunculated polyp, while 16 had sessile polyps. A total of 55.17% had non-advanced pedunculated polyp, 22.41% had non-advanced sessile polyp, 17.24% had advanced grade pedunculated polyp, while the remaining 5.17% had advanced grade sessile polyp. Histopathological findings revealed that 44.83% of the participants had tubular adenoma with low grade dysplasia (LGD) among the non-advanced pedunculated polyps’ cases, 17.24% had tubular adenoma with LGD among the non-advances sessile cases. Among the advanced pedunculated polyps’ cases, 6.90% had tubular adenoma with high grade dysplasia (HGD), 3 (5.17%) had villous adenoma with dysplasia, and 2 (3.45%) had tubulovillous with dysplasia. Among the 3 advances sessile polyps cases, 3.45% had tubular adenoma with HGD, while 1 patient had malignancy. Conclusions: It was observed that FIT positive patients had a higher frequency of pedunculated polyps, specifically advanced pedunculated polyps. Both sessile and pedunculated polyps had a high prevalence among patients aged between 50-59 years.